Sustainable Concrete Bricks Partially Comprised of Supplementary Cementitious Material and Alternative Fine Aggregate- A Review - ABDUL MUHAIMIN BIN ABU BAKAR (Progress in Engineering Application and Technology, 2021)
T he usage of cement and normal fine aggregates, sand is tended to give pollution to this world. Researchers finds that there are many materials or substances that can replace them. Most of the materials are waste materials and non-pollution materials. The potential of using this material of alternative fine aggregates and supplementary cementitious materials will produce more sustainable concrete bricks in the future. In this paper, an optimum percentage of partial fine aggregates and supplementary cementitious materials of the sustainable concrete bricks will be observed. Then the mechanical properties such as compressive strength and water absorption of the sustainable conrete bricks will be compared. This will help other researchers and construction industry to produce more eco-friendly brick that can perform as conventional bricks.